Riesgo de suicidio y factores asociados en la comunidad indígena Tikuna (2023)
This research focuses on the study of factors associated with the risk of suicide in the Tikuna indigenous community, as this problem has occurred in many indigenous communities throughout history, becoming a public health issue due to high suicide rates (Vargas, 2016).